VD_FINDINFO Décision / 2014 / 998 vom 11. November 2014 - VD Tribunal cantonal (2014)
DIFFAMATION, CALOMNIE, DÉNONCIATION CALOMNIEUSE, CLASSEMENT DE LA PROCÉDURE | 173 CP, 174 CP, 303 CP, 310 CPP (CH), 393 CPP (CH)